The Relationship of Home Physical Environment and Family History with Pulmonary Tuberculosis in Gunung Tabur - Isworo, Yannie; Prasasti, Alfi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
Tuberculosis (TB) is a contagious lung infection that remains a significant public health problem, with a total of 92 cases reported in the Gunung Tabur Health Center working area. Physical environmental conditions of the household and family history are suspected to influence the transmission of this disease. This study employed a quantitative approach with a cross-sectional design. The research sample comprised 48 respondents, selected using a simple random sampling technique from the population of pulmonary TB patients. Data were collected through observation, interviews, and questionnaires, and subsequently analyzed using the Chi-Square test. The analysis revealed a significant relationship between air humidity (p = 0.049) and room temperature (p = 0.038) and the incidence of pulmonary TB. In contrast, no significant relationships were observed for lighting (p = 0.098), residential density (p = 0.078), and family history (p = 0.670). In conclusion, household physical environmental conditions, particularly suboptimal air humidity and room temperature, are associated with the incidence of pulmonary TB in the Gunung Tabur Health Center working area.